1997
DOI: 10.1002/(sici)1097-4547(19970115)47:2<144::aid-jnr3>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory volume decrease and associated osmolyte fluxes in cerebellar granule neurons are calcium independent

Abstract: To investigate a possible role for Ca as a transduction signal for regulatory volume decrease (RVD), the effects of external Ca removal, Ca channel blockers (Cd, Co, La, Gd, verapamil, diltiazem, dihydropyridines), and inhibitors of endoplasmic reticulum Ca release (dantrolene, ryanodine, TMB‐8) were examined on RVD and on the swelling‐activated efflux of two main osmolytes: Cl (traced by 125I) and [3H]taurine. Omission of Ca plus EGTA did not affect RVD or osmolyte release but when BAPTA was the chelator, RVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Several earlier studies have addressed the cell volume changes induced by anisotonicity and have described volume regulatory mechanisms dependent on or independent of [Ca 2+ ] i [21,25]. Assuming that cells should respond similarly to volume alterations under anisotonic or isotonic conditions, it is not clear why after brain injury and in other pathological states, cells do not regulate their volume.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies have addressed the cell volume changes induced by anisotonicity and have described volume regulatory mechanisms dependent on or independent of [Ca 2+ ] i [21,25]. Assuming that cells should respond similarly to volume alterations under anisotonic or isotonic conditions, it is not clear why after brain injury and in other pathological states, cells do not regulate their volume.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we and others had demonstrated that increases in [Ca 2ϩ ] i or in PKC activity are not prerequisites for the basal (swelling-induced) release of organic osmolytes such as taurine and D-aspartate from neurotumor cells, neurons, or astrocytes (Moran et al, 1997;Mongin and Kimelberg, 2002;Cardin et al, 2003;Loveday et al, 2003;Cheema et al, 2005). Likewise, in the present study, we observed that, at least under mildly hypotonic conditions, the basal release of 125 I Ϫ also appears to be essentially independent of Ca 2ϩ availability and PKC activity.…”
Section: Discussionmentioning
confidence: 99%
“…In cerebellar astrocytes and granule neuron cells, changes in [Ca 2+ ] i and RVD are not related; thus, [Ca 2+ ] i is thought to be irrelevant as a transduction signal for RVD [30,31]. In endothelial cells, changes in [Ca 2+ ] i and hypotonicity-induced current are not related and is independent of [Ca 2+ ] i [32].…”
Section: Discussionmentioning
confidence: 99%